Simulation and analysis of the solidification characteristics of a Si-Mo ductile iron - Çelik G.A.; Tzini M.-I. T.; Polat Ş.; Aristeidakis J S.; Atapek Ş.H.; Sarafoglou P.I.; Haidemenopoulos G.N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
High silicon and molybdenum ductile cast irons (Si-Mo alloys) are commonly used as exhaust manifold materials suffering from high temperature-oxidation and thermal-mechanical fatigue. The structural integrity of cast Si-Mo alloys under these service conditions is attributed to their microstructure consisting of spheroidal graphite and Mo-rich carbide embedded in a ferritic matrix. However, the cast structure includes also pearlite structure having a detrimental effect on the mechanical properties, therefore the cast matrix needs to be heat treated. In this study, the solidification of a Si-Mo ductile iron was investigated using (i) thermodynamic and kinetic calculations by Thermo-Calc and DICTRA software and (ii) thermal analysis in order to reveal out the sequence of phase formation and the phase transformations during solidification and (iii) microanalysis by energy dispersive spectrometer in order to determine elemental segregation and compare with the calculated values. The solidified structure was also characterized and all microstructural features were specified.